Perfil clínico-epidemiológico, fatores de risco e qualidade de vida de pacientes com disfunção das glândulas de Meibomius - Duarte, Thaissa Faloppa (2024)
Introduction: Meibomian gland dysfunction (MGD) is a chronic, multifactorial abnormality characterized by obstruction of the terminal duct and/or qualitative and quantitative changes in glandular secretion. Objective: To investigate the clinicalepidemiological profile, risk factors and quality of life of patients with Meibomius gland dysfunction. Casuistic and Method: A total of 108 patients with MGD were prospectively studied. The analyzed variables included demographic (sex, age, and education level) and clinical (cardiovascular, dermatological, rheumatological and gynecological history, family history of cardiovascular disease). Symptoms of dry eye were assessed using Ocular Surface Disease Index (OSDI) questionnaire. Eyelid disorders such as margin, vascularity, cilia, mucocutaneous junction, and Meibomius glands (MG) orifices were analyzed. Secretory function was studied through expressibility and secretion quality. Dry eye propaedeutic tests included quantification of blinking and blinking interval, measurement of the lower tear meniscus, TBUT, fluorescein staining, and Schirmer test. Laboratorial exams included fasting glucose, glycated hemoglobin (GH), total cholesterol (TC), cholesterol of low-density lipoprotein (LDL-c), cholesterol of high-density lipoprotein (HDL-c) and triglycerides (TG). Life quality was analyzed using OSDI questionnaire. Results: Among the 108 patients studied, mean age was 53.6 ± 17.9 years, 69.4% were females, 70.4% had higher education, 82.7% gynecological, 16.7% dermatological, 13.9% rheumatological, 46.3% cardiovascular history, and 80.6% had family history of cardiovascular disease. Symptoms were mild (28.7%) or moderate (38%); pruritus and/or discomfort were more frequent (63.9%). Most of the patients showed slightly thickened eyelid margin (44.4%), vascularity E2 (36.2%), crusted and oily eyelashes (61.1%), orifices with mild obstruction (30.6%) and posterior mucocutaneous junction (74.1%), and all functional glands (59.8%). Mean of meniscus height was 0.3 ± 0.1 mm, 53.7% of the patients not stain with fluorescein and 48.1% showed 15/15 in the Schirmer test. Regarding clinical severity of patients with MGD, 34.3% was mild, 34.3% moderate and 31.4% severe. In 11.3% and 19.6% of the patients, high fasting glucose and GH levels, respectively, were found; in 34.7%, 33.3%, 27.8%, and 28.9% of them, high TC, HDL-c, LDL-c, and TG levels, respectively were registered. There was association among clinical severity and gynecological (P=0.001), cardiovascular (P=0.006) history, and life quality (P<0.001). Conclusions: MGD was predominant in female and in the fifth decade of life. The most frequent symptoms are pruritus and eye discomfort with moderate intensity. Slightly thickened eyelid margin, moderate increase in vascularization, crusted and oily eyelashes, holes with mild or normal obstruction, and in the posterior mucocutaneous junction are more frequent. Most patients had all functional Meibomian glands, clear fluid secretion, and signs of evaporative dry eye. Serum levels of fasting glucose, HG, TC, HDL-c, LDL-c and TG may be altered in patients with GDM. Most patients with MGD had worse quality of life. Sex was associated with life quality and HDL-c. Patients with dermatological, gynecological, cardiovascular history, morphological alterations, fasting glucose, HG, TC, and life quality presented a significant association with age. There was association among clinical severity and gynecological, cardiovascular history, and quality of life.